Representation of understanding of islamic values into the choice of hijab and fashion trends among islamic religious education students of the faculty of tarbiyah - Hanan; Mad Sa’i (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This study aims to examine the representation of understanding of Islamic values ​​​​in relation to hijab and fashion trends among female students of the Islamic Religious Education (PAI) Study Program, Faculty of Tarbiyah, UIN Madura. The focus of the study is directed at three main aspects, namely: (1) female students' understanding of Islamic values ​​​​in selecting hijab and fashion trends, (2) representation of this understanding in the classification of fashion choices, and (3) factors that influence their clothing trend preferences. This study uses a qualitative approach with descriptive methods. Data sources were obtained from semi-structured interviews with lecturers, the code of ethics team, the head of the study program, the secretary of the study program, and female students in the third to eighth semesters, supplemented by structured non-participant observation, field documentation, and online questionnaires. Data analysis was carried out through reduction, presentation, and drawing conclusions, while data validity was maintained by triangulation of sources, methods, extended participation, and diligent observation. The results of the study indicate a diversity of understanding and application of Islamic values ​​​​in selecting hijab and fashion. Some female students place Islamic law as a primary consideration, by choosing loose-fitting sharia clothing, completely covering the aurat, and reflecting the identity of devout Muslim women. Meanwhile, others prioritize comfort, adapting to modern trends, and practical aspects of clothing, without completely abandoning the principle of modesty. These choices are divided into sharia-compliant, semi-formal, and casual clothing categories, each reflecting the dynamic interpretation of Islamic values. Factors influencing preferences include internal factors (religious awareness, educational background, spiritual motivation) and external factors (social environment, social media, and economic conditions).